Un largo proceso en la definición historiográfica de las fuentes del arte medieval: el arte antiguo como referente para la escultura románica - José Alberto Moráis Morán (Medievalista)
In this article it is reflected on the principal historiographic contributions around the study of the ancient legacy present in the Romanesque sculpture. Since the appearance of the "Romanesque" term, coined by Charles de Gerville in 1818, until the publication in 1960 of the Erwin Panofsky´s book Renaissance and Renascences in Western Art, it was advanced a lot in the definition of such influences. Actually it is tried to present a synchronous panorama that allows to put into context the current researches on this highly topical subject.